THE EFFECT OF AN EDUCATIONAL CURRICULUM ACCORDING TO THE (KUD) STRATEGY ON LEARNING SOME BASIC SKILLS AMONG MIDDLE SCHOOL FOOTBALL PLAYERS - Hassan Jassim Al-Bahadli (Proximus Journal Publishing, 2024)
The objective of the research is to prepare educational units for strategy. Contending For learners the intermediary phase within the Directorate of Education of Al-Majar Al-Kabir. Assess the influence of the KUD method on specific talents. Fundamental Football for Learners Middle school of the Directorate of Education of Al-Majar Al-Kabir. Concerning research technique and field methods, the researcher employed the experimental method to address the study's problem. The investigator ascertained Scholarly Community Who is the individual? Middle school students in the Directorate of Maysan Education, Al-Majar Al-Kabir Aden medium for males the total enrolment of 77 students during the academic year 2023-2024. The research sample of 30 students, randomly assigned into two groups of 15 each, one of which was experimental and implemented the educational program according to the KUD technique. The other is an officer to whom the standard procedure has been implemented. Subsequently, the pre-tests were administered. and the researcher developed 16 educational units for the experimental group, delivering two units weekly on Mondays and Thursdays, in accordance with the school's established schedule. These units were presented to experts and specialists in teaching methodologies and football to solicit their opinions and observations regarding the suitability of implementing this strategy in the prepared educational units. The curriculum persisted. Instructional The researcher used the necessary statistical methods to the study sample using the SPSS software, and in the third chapter, presented, analyzed, and discussed the results utilizing their own tables. Summaries In the fourth chapter, the researcher concludes that the implementation of the educational curriculum based on the (KUD) strategy has resulted in a notable enhancement of certain fundamental football skills. Significant differences were observed in the pre- and post-study tests of the variables for both the control and experimental groups, favoring the post-assessments. He also addressed the key recommendations, including the implementation of a strategy (KUD) for students' acquisition of football skills (both fundamental and advanced) and the execution of analogous studies based on the strategy (KUD) across various age demographics and in other sports disciplines
Keywords: Strategy; Basic football skills; Middle school players